PELATIHAN BISNIS DIGITAL DI SMK BOEDI LUHUR BEKASI - Widodasih, Wening Ken; Permana, Indra; Rochayata, Kurbandi Satpatmantya Budi (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
This digital business training program is a PKM program conducted at SMK Boedi Luhur emerged as a successful initiative in shaping students into individuals who are responsive to technological developments and business competition in the digital age. Through Project Based Learning methods, Workshops, and Seminars, the program successfully stimulates students' interest and identifies their talents in various aspects of digital business. The students' success in completing digital business projects not only reflects quality academic achievement, but also has a positive impact on SMK Boedi Luhur's reputation as a progressive educational institution. Industry recognition, media reports, and successful student testimonials reinforce the impression that SMK Boedi Luhur is a quality educational center and responsive to the needs of the job market. The improved reputation of the school is also reflected in growing student enrollment and community demand. This program opens the door for students to achieve success in the digital business world, making SMK Boedi Luhur a container that produces empowered and competent individuals. Through close ties to industry, community involvement, and resounding alumni achievements, SMK Boedi Luhur is proving itself to be an educational institution capable of shaping the future of students in the dynamic digital age.